Sovereign Defaults and Debt Sustainability: The Debt Recovery Channel - Ibrahima Diarra; Michel Guillard; Hubert Kempf (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper focuses on the debt recovery channel linking the dynamics of public debt to partial sovereign defaults. We build a simple model which incorporates sovereign default and a debt recovery rule. It depends on a parameter that allows for partial debt recovery. We show that the maximum debt-to-GDP ratio that a country can sustain without defaulting is increasing, nonlinear, and sensitive to the debt-recovery parameter. A higher debt recovery parameter increases the fiscal space but worsens the financial position of a borrowing country after a default episode. We show the empirical relevance of this channel for estimating country-specific fiscal spaces.
Keywords: 330